2021
DOI: 10.1002/cpz1.143
|View full text |Cite|
|
Sign up to set email alerts
|

Electrophysiologic Analysis of Tight Junction Size and Charge Selectivity

Abstract: Tight junctions form selectively permeable barriers that limit paracellular flux across epithelial‐lined surfaces. Rather than being absolute barriers, tight junctions in many tissues allow ions, water, and other small molecules to cross on the basis of size and charge selectivity via the high‐capacity pore pathway. Most probes currently used to assess tight junction permeability exceed the maximum size capacity of the pore pathway. As a result, available analytical tools have generally been limited to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…TNFα can operate as an activator for MLCK, in turn leading to the increased permeability of the paracellular barrier [18]. Regarding a changed TJ barrier function, different routes can be involved, in particular the low-capacity leak and the high-capacity pore pathways [40,41]. The low-capacity leak pathway allows macromolecules to cross the TJ barrier, and is involved when TNFα stimulates MLCK [18].…”
Section: Discussionmentioning
confidence: 99%
“…TNFα can operate as an activator for MLCK, in turn leading to the increased permeability of the paracellular barrier [18]. Regarding a changed TJ barrier function, different routes can be involved, in particular the low-capacity leak and the high-capacity pore pathways [40,41]. The low-capacity leak pathway allows macromolecules to cross the TJ barrier, and is involved when TNFα stimulates MLCK [18].…”
Section: Discussionmentioning
confidence: 99%
“…After equilibration, potential differences were measured before and during application of a 50-μA current. Transepithelial short-circuit current (Isc) and transepithelial resistance (TER) were calculated using Ohm’s law, as previously described (2, 43).…”
Section: Methodsmentioning
confidence: 99%
“…The tricellular tight junction proteins tricellulin and angulin 1 might also be important regulators of leak pathway permeability. In vitro studies have shown that deletion of either tricellulin or angulin-1 increases leak pathway permeability [146][147][148] . Similar to tricellulin, siRNAmediated knockdown of the other TAMPs, MARVELD3 (refs.…”
Section: The Leak Pathway In Diseasementioning
confidence: 99%